Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pengunjung di Kebun Raya Calina Bato Kabupaten Sumenep - Reza Maulana; Deykha Aguilika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to examine the impact of service quality and facilities on the level of visitor satisfaction at Calina Bato Botanical Garden, Sumenep Regency. The approach method is quantitative with data collected through a Likert scale-based closed questionnaire. The purposive sampling technique was used to determine the sample, resulting in 100 respondents who met certain criteria. The data were analyzed using multiple linear regression methods and t tests with the help of SPSS. Service quality and facilities stated a positive and significant impact on visitor satisfaction. These findings provide important insights for Calina Bato Botanical Garden managers to improve services and facilities, which in turn can support the development of the tourism sector in the region.